2022
DOI: 10.7759/cureus.21740
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine-Related Myocarditis: A Descriptive Study of 40 Case Reports

Abstract: After the surging rise in the Coronavirus disease 2019 (COVID-19) pandemic, the Food and Drug Administration (FDA) approved emergency approval of vaccinations to prevent life-threatening complications of COVID-19 infection. These vaccines are BNT162b2, mRNA-1273. Later, the FDA also approved JNJ-78436735. COVID-19 vaccination does not have major side effects, but there are some concerning adverse events reported right after vaccination. Myocarditis is one of them. Based on our analysis of 40 case reports, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 26 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…Overall, 266 publications were retrieved for review of full‐text articles. Finally, 102 publications, including 56 case reports 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 92 , 93 , 94 , 97 , 98 , 101 , 102 , 105 , 106 an...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, 266 publications were retrieved for review of full‐text articles. Finally, 102 publications, including 56 case reports 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 92 , 93 , 94 , 97 , 98 , 101 , 102 , 105 , 106 an...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 468 patients with suspected myocarditis and cardiac MRI findings were included in this study ( n = 294 from case reports/case series with IPD 5 , 7 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to the milder clinical course compared to classic MYO and MIS-C MYO, strong pharmacologic support is only rarely required in patients with COVID-19 vaccine-related MYO. Use of non-steroidal anti-inflammatory drugs, immune globulin (IVIG), and steroids is not common ( 48 ) and remains controversial ( 49 ). A pediatric study comparing drug use in patients with viral MYO, MIS-C MYO and vaccine-related MYO has shown that intravenous immunoglobulin (IVIG) and steroids were frequently used in patients with classic MYO and MIS-C MYO but in only one and in none of the 9 patients with previous COVID-19 immunization ( 50 ).…”
Section: Clinical Characteristics and Outcome Of Myocarditis Associat...mentioning
confidence: 99%